2020
DOI: 10.1609/aaai.v34i02.5579
|View full text |Cite
|
Sign up to set email alerts
|

Strategy-Proof and Non-Wasteful Multi-Unit Auction via Social Network

Abstract: Auctions via social network, pioneered by Li et al. (2017), have been attracting considerable attention in the literature of mechanism design for auctions. However, no known mechanism has satisfied strategy-proofness, non-deficit, non-wastefulness, and individual rationality for the multi-unit unit-demand auction, except for some naïve ones. In this paper, we first propose a mechanism that satisfies all the above properties. We then make a comprehensive comparison with two naïve mechanisms, showing that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…In contrast, under a network structure, to protect the benefit of the buyers, we may hide the sale information from their descendants. Kawasaki et al [2020] first considered non-wastefulness in social networks. We will also define non-wastefulness in our setting.…”
Section: The Model and Standard Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, under a network structure, to protect the benefit of the buyers, we may hide the sale information from their descendants. Kawasaki et al [2020] first considered non-wastefulness in social networks. We will also define non-wastefulness in our setting.…”
Section: The Model and Standard Definitionsmentioning
confidence: 99%
“…Mechanism design in social networks has become an active research area [Li et al 2017[Li et al , 2018Zhao et al 2018;Kawasaki et al 2020;Xu and He 2020]. The classical auctions only sell items to buyers directly connected to the seller and do not consider spreading the commodity information through the network links between buyers to get possibly higher utilities [Nisan et al 2007;Bajari and Hortacsu 2003].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these works consider little about agents' incentive design and equilibrium reasoning with the social interactions. Besides the query incentive network problems, there have been some very recent works on mechanism design in social networks [Li et al, 2017, Zhao et al, 2018, Jeong and Lee, 2020, Kawasaki et al, 2020. As far as we know, all these works concentrate on introducing social networks into typical auction problems which are quite different from contest design and these works do not treat graph based BNE analysis as their central problem.…”
Section: Related Workmentioning
confidence: 99%
“…Another more challenging open question is to design similar mechanisms for multiple heterogeneous items settings. It has been shown that the problem becomes extremely difficult when we move just one step forward from single-item to multiple homogeneous items cases [20,51]. The difficulty comes from the fact that the allocation and price of one participant can be easily influenced by its invitees and siblings [51].…”
Section: Resource Allocationmentioning
confidence: 99%